Child Criminal Justice Reconstruction System (As the efforts of Children's Rights in conflict with the Press Law According to Legal Aid) - Adi Mansar (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Third Amendment to Article 1 Paragraph (3) confirms that "The State of Indonesia is a State of Law". Indonesia the rule of law originating from Pancasila and 1945 Constitution as stipulated in the People's Consultative Assembly of the Republic of Indonesia Number III / MPR / 2000 Concerning Legal Sources and Order of Laws and Regulations. The basic rights stipulated in the constitution have then been regulated in several legislative regulations, for example Law Number 11 Year 2012 concerning the Juvenile Justice System in Consideration letter a reads "that the child is the trust and gift of God Almighty who has dignity and dignity as complete be a human". The letter b stated that "in order to maintain their dignity and status, children are entitled to special protection, especially legal protection in the justice system. Problem Formulation of How the Legal Arrangement of the Criminal Justice System for Children in Indonesia, How to Legal Instruments for the Protection of Children in Criminal Law. Fulfillment of the Rights of Children in conflict with the law should have been guaranteed since the child began to be determined as a suspect until the child began to carry out punishment/ guidance in Special Child Development Institute. .Recommendation of our Criminal System which is oriented towards coaching according to the purpose of punishment (objective theory) wherever possible provides education to children so that it is truly changing and aware. The Criminal Justice System for Children needs to be reconstructed specifically regarding the pattern of providing legal assistance, financing and special space for children in each prison, remand center in Indonesia. Child protection legal instruments in criminal law need to be updated, especially law enforcement with a miserable approach for children, so restorative justice needs to be grounded. Keywords: